Wernicke Encephalopathy Related to Hyperemesis Gravidarum: A Retrospective Study of 12 Cases - Kaouthar Abouelbaqua; Houssam Rebahi; Nisrine Louhab; Najib Kissani; Ahmed Rhassane El Adib (Case Reports in Critical Care)
Conclusion: In HG, thiamin rapidly depletes which can lead to WE with adverse outcomes for the mother and fetus. Therefore, physicians must be vigilant in detecting early signs of WE to promptly provide a high dose of thiamin with targeted multimodal therapies as this could be lifesaving.